Quantifying Short-Term Erosion and Deposition in an Active Gully Using Terrestrial Laser Scanning: A Case Study From West Tennessee, USA - Li, Yingkui; McNelis, John J.; Washington-Allen, Robert A. (Frontiers in Earth Science, 2020)
High-resolution terrestrial laser scanning (TLS) provides a unique opportunity to monitor short-term erosion and deposition processes in gully systems. This study quantified the pattern of erosion and deposition within an active gully in the sub-tropical environment of west Tennessee. Two TLS surveys were conducted on December 2014 and February 2015 to generate digital elevation models (DEMs) of different resolutions. The volumes of erosion and deposition were estimated by differencing the DEMs of these two dates with consideration of the spatially propagated errors associated with TLS-measured gully topography. The detected erosional and depositional volumes were 11.0 and 8.2 m3, respectively, with a net loss of 2.8 m3 of sediment at the DEM resolution of 2-cm. We found that both estimated volumes of erosion and deposition decrease as the DEM resolution becomes coarser. The estimated erosional volume decreases at a relatively high rate because erosion mainly occurs on steeper slopes where the propagated errors in TLS-measured topography are relatively higher, leading to rapid smoothing at coarser resolutions. In contrast, the depositional areas on gentler slopes have less propagated errors. This bias in the smoothing behavior of erosional and depositional areas appears to make coarser resolution DEMs dominated by deposition, a misleading interpretation of the sediment dynamics within the gully. We therefore suggest caution when using DEM difference to interpret the erosion-deposition processes within a gully system.